Factors, Determine the Psychology Students’ Professional Conceptions and Competence - Kordunova, Natalia Aleksandrovna (Psychological Prospects Journal, 2012)
The article analyzes theoretical approaches and concepts as well as results of assessment of such factors that determine the professional conceptions and competence of psychology students.